Evaluating Coaching Intervention for Financial Risk Perception and Credit Risk Management in a Nigerian Sample - Ugwoke, Robinson Onuora; Onyeanu, Edith Ogomegbunam; Ugwoke, Obioma Vivian; Ajayi, Tijani Ahmed (Frontiers in Psychology, 2022)
There is no doubt that a negative perception of financial risk and a lack of credit risk management adversely impact business growth and business owners' wellbeing. Past studies suggest that most Nigerian traders have poor risk perceptions and manage risk poorly. A business coaching program within rational-emotive behavior therapy framework (REBT-based business coaching) was evaluated in order to determine its effects on financial risk perception and credit risk management among Nigerian traders. This study used an open-label parallel randomized control design. This 8-weeks coaching program had sixty traders in the REBT-based business coaching group and fifty-nine traders in the control group. The mixed-model repeated measures ANOVA was utilised for analysis of the study data. Results show that relative to a control group, traders' financial risk perception (F(1.09,127.15)=637.29, p<.001, ω²=0.69) and credit risk management (F(1.55,181.22)=795.51, p<.001, ω²=0.80) significantly improved after participating in REBT-based business coaching program. This study shows that REBT-based business coaching program is integral to increasing financial risk perception and credit risk management among Nigerian traders. This study contributes to the advancement of business coaching program within the rational-emotive behavior therapy framework for market traders, and its application in similar situations. The study considered the benefits of business coaching program for market traders from a developing country, which is a rarely studied group. It is highly recommended that professionals study the relationship between REBT-based business coaching and economic decision-making within various organizational contexts.